Self-Determination in the International Legal System Whose Claim, to What Right? - Sparks, Tom (Bloomsbury Academic, 2023)
This book provides a new framework for self-determination in four categories: polity-based, identitarian, colonial, and remedial forms, bringing much-needed clarity to this key question in international law.